2000
DOI: 10.1080/13682199.2000.11784358
|View full text |Cite
|
Sign up to set email alerts
|

Colour difference acceptability for calibrated digital images

Abstract: Abstract:The aim of this research work is to establish what level of numeric colour difference between two digital images is visually acceptable by average human observers on a calibrated monitor under a fixed set of viewing conditions. A visual ordinal category method is introduced and a description of the experimental design is provided. Results based on over 4000 visual and numeric comparisons are reported. All results are analysed by statistical methods. The correlation between visual assessments and numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The size of the quoted delta E values may be interpreted by reference to the visual matching experiments of Yu and Oulton, 13 where object to image visual colour differences are quantified in terms of CMC (2 : 1) delta E. They found that a measured delta E(1 was typically reported as an acceptable colour match, and any difference delta E>3 was regarded as a poor match.…”
Section: Human Observer Resultsmentioning
confidence: 99%
“…The size of the quoted delta E values may be interpreted by reference to the visual matching experiments of Yu and Oulton, 13 where object to image visual colour differences are quantified in terms of CMC (2 : 1) delta E. They found that a measured delta E(1 was typically reported as an acceptable colour match, and any difference delta E>3 was regarded as a poor match.…”
Section: Human Observer Resultsmentioning
confidence: 99%
“…Instead, it aimed at being included as a useful color reference in high-end photography of objects [30]. It soon indeed became the de facto standard in high end photography [31], and even today it remains to be so in professional photography under the name X-Rite ColorChecker Classic [14]. When digital cameras became popular it was found that the MacBeth ColorChecker was less suitable for this task, as the colors of this chart cover only a relatively small color gamut [30].…”
Section: A) Original Colorcheckermentioning
confidence: 99%
“…As mentioned, the cameras were of the type normally used by the retailer for security purposes, and earlier trials found that the focusing and angle of the in-store cameras were critical. Independent research Yu and Oulton (2000) has demonstrated that the quality of the image generated by the video cameras was vital to successful analysis. Because of the time-lapse function, the system only provided image quality with an approximate sampling rate of 5 frames per second.…”
Section: Data Collectionmentioning
confidence: 99%